CLINICAL, NEUROLOGICAL AND DIAGNOSTIC ASPECTS OF ACQUIRED PRECEREBRAL ANGIODYSPLASIAS - Khalimova, H.M.; Rakhmatullaeva, G.K.; Khudayarova, S.M.; Parpieva, Yu.R. (Toshkent tibbiyot akademiyasi axborotnomasi, 2020)
Precerebral angiodysplasia can be not only congenital, but also acquired. Acquired precerebral angiodysplasia most often develop as a result of arterial hypertension, atherosclerosis, and spinal injuries. The given case from practice is proof of this. Patient against GB, cerebral arteriosclerosis, was disturbed for several years, headaches, dizziness, decreased vision, increased blood pressure, with increased blood pressure, symptoms intensified, a veil appeared in front of the eyes, a blind spot that passed by itself, as a result, ONMK developed. Subsequently, 2 page kicking of the ICA was diagnosed.